Jets, arcs, and shocks: NGC5195 at radio wavelengths - Rampadarath, H; Soria, R; Urquhart, R; Argo, MK; Brightman, M; Lacey, CK; Schlegel, EM; Beswick, RJ; Baldi, RD; Muxlow, TWB; McHardy, IM; Williams, DRA; et al. (Oxford University Press, 2018)
We studied the nearby, interacting galaxy NGC5195 (M 51b) in the radio, optical and X-ray bands.We mapped the extended, low-surface-brightness features of its radio-continuum emission; determined the energy content of its complex structure of shock-ionized gas; constrained the current activity level of its supermassive nuclear black hole. In particular, we combined data from the European Very Long Baseline Interferometry Network (∼1-pc scale), from our new e-MERLIN observations (∼10-pc scale), and from the Very Large Array (∼100–1000-pc scale), to obtain a global picture of energy injection in this galaxy. We put an upper limit to the luminosity of the (undetected) flat-spectrum radio core. We find steep-spectrum, extended emission within 10 pc of the nuclear position, consistent with optically thin synchrotron emission from nuclear star formation or from an outflow powered by an active galactic nucleus (AGN). A linear spur of radio emission juts out of the nuclear source towards the kpc-scale arcs (detected in radio, Hα and X-ray bands). From the size, shock velocity, and Balmer line luminosity of the kpc-scale bubble, we estimate that it was inflated by a long-term-average mechanical power ∼3–6 × 10^41 erg s^−1 over the last 3–6 Myr. This is an order of magnitude more power than can be provided by the current level of star formation, and by the current accretion power of the supermassive black hole.We argue that a jet-inflated bubble scenario associated with previous episodes of AGN activity is the most likely explanation for the kpc-scale structures.